Bottom‐Up Construction of Porous Organic Frameworks with Built‐In TEMPO as a Cathode for Lithium–Sulfur Batteries. Issue 14 (26th June 2017) - Zhou, Baolong; Hu, Xiang; Zeng, Guang; Li, Shiwu; Wen, Zhenhai; Chen, Long
Abstract: Two redox‐active porous organic frameworks (POFs) with a built‐in radical moiety (TEMPO) and hierarchical porous structures were synthesized through a facile bottom‐up strategy and studied as cathode materials for lithium–sulfur (Li−S) batteries. The sulfur loading in these two POFs reached 61 %, benefitting from their large pore volumes. Owing to the highly dense docking sites of TEMPO, sulfur could be covalently immobilized within the porous networks and efficiently inhibit the shuttle effect, thereby significantly improving the cycling performance. The composites TPE‐TEMPO‐POF‐S (TPE=tetraphenylethene) deliver a capacity in excess of 470 mAh g −1 after 200 cycles with a coulombic efficiency of around 100 % at a current rate of 0.1 C. Furthermore, TEMPO‐POFs with sulfur embedded showed excellent rate capability with limited capacity loss at rates of 0.1–1 C. Abstract : Keep the TEMPO : Stable porous organic frameworks (POFs) with a built‐in radical moiety (TEMPO) were prepared by a bottom‐up strategy. These TEMPO‐POFs were applied as host cathode materials for Li−S batteries with good cycling performance. Furthermore, TEMPO‐POFs with sulfur embedded showed excellent rate capability with limited capacity loss at rates of 0.1–1 C.